2013
DOI: 10.1136/annrheumdis-2012-203046
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of open-label etanercept on extended oligoarticular juvenile idiopathic arthritis, enthesitis-related arthritis and psoriatic arthritis: part 1 (week 12) of the CLIPPER study

Abstract: ObjectiveTo investigate the efficacy and safety of etanercept (ETN) in paediatric subjects with extended oligoarticular juvenile idiopathic arthritis (eoJIA), enthesitis-related arthritis (ERA), or psoriatic arthritis (PsA).MethodsCLIPPER is an ongoing, Phase 3b, open-label, multicentre study; the 12-week (Part 1) data are reported here. Subjects with eoJIA (2–17 years), ERA (12–17 years), or PsA (12–17 years) received ETN 0.8 mg/kg once weekly (maximum 50 mg). Primary endpoint was the percentage of subjects a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
0
6

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 116 publications
(76 citation statements)
references
References 32 publications
5
64
0
6
Order By: Relevance
“…42 Of the remaining four studies, three were not relevant, as they were single-arm studies, and a fourth was a RCT reported in a conference abstract 98 with only limited detail available. However, one of the single-arm studies -the CLIPPER study 99 -is noteworthy as it focuses specifically on the JIA subtypes that were absent from the pivotal Lovell and colleagues trial, 42 namely EO JIA, ERA and PA. Details are presented in Additional supporting evidence.…”
Section: Review Of Pfizer Ltd Company Evidence Submission For Etanerceptmentioning
confidence: 99%
See 2 more Smart Citations
“…42 Of the remaining four studies, three were not relevant, as they were single-arm studies, and a fourth was a RCT reported in a conference abstract 98 with only limited detail available. However, one of the single-arm studies -the CLIPPER study 99 -is noteworthy as it focuses specifically on the JIA subtypes that were absent from the pivotal Lovell and colleagues trial, 42 namely EO JIA, ERA and PA. Details are presented in Additional supporting evidence.…”
Section: Review Of Pfizer Ltd Company Evidence Submission For Etanerceptmentioning
confidence: 99%
“…99 This is a single-arm, Phase-IIIb open-label, multicentre interventional study funded by Wyeth (subsequently acquired by Pfizer Inc.). The study was designed to assess the safety and efficacy of etanercept in children and adolescents with three JIA subtypes classified using the ILAR criteria: EO, ERA and PA.…”
Section: Enthesitis-related Arthritis and Psoriatic Arthritismentioning
confidence: 99%
See 1 more Smart Citation
“…Так, в 2007 г. было опубликовано 23 статьи, а спустя 10 лет, в 2017 г., -22 статьи в рецен-зируемых иностранных журналах в сети PubMed (ключе-вые слова: etanercept, JIA) [19]. Помимо крупных много-летних многоцентровых исследований, направленных на изучение отдаленной эффективности и безопасности [20,21], ежегодно детские ревматологи разных стран публикуют данные как локальных регистров, так и реги-стров, охватывающих пациентов целого государства [6,22]. Интерес ревматологов к результатам, полученным из реальной клинической практики, связан с тем, что в большие многоцентровые клинические исследования включаются далеко не все пациенты.…”
Section: обсуждение основного результата исследованияunclassified
“…In addition to nonsteroidal antiinflammatory drugs (NSAIDs), children with ERA are often treated with sulfasalazine (SSZ) 9, methotrexate (MTX), and glucocorticoids. Several studies suggest that biologic agents, specifically tumor necrosis factor (TNF) inhibitors, improve ERA symptoms 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22.…”
Section: Introductionmentioning
confidence: 99%